Synthesis and Thermoresponsive Characterization of Poly(2-(dimethylamino) ethyl methacrylate) Polymers - Karis, Dylan G.; Bol, Austin R.; Farrell, Michael (My University, 2013)
Poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) is a smart polymer. "Smart" polymers have the unique ability to aggregate under certain conditions such as pH, temperature, and/or concentration. The purpose of this study was to synthesize samples of PDMAEMA.
Color poster with text, diagrams, photographs, images, graphs, charts, and tables.
Keywords: Polymeric composites; Posters